PKM PENGUATAN PEMBELAJARAN DEEP LEARNING DAN IMPLEMENTASI MEDIA PEMBELAJARAN DIGITAL PADA SDN 01 LIMA KAUM - Sri Wahyu Neka; Sunarti Sunarti (CV. DIGITIAL EDUKASI NUSANTARA, 2025)
This Community Service Program was conducted to strengthen teachers’ pedagogical competence and digital literacy through the implementation of deep learning approaches and digital learning media at SDN 01 Lima Kaum. The situational analysis revealed that classroom instruction was still predominantly teacher-centered, characterized by limited use of digital media and low integration of meaningful learning that promotes higher-order thinking skills among students. The program was implemented through several stages, including preparation, deep learning training, digital learning media development workshops, classroom implementation mentoring, and evaluation. The results indicated an improvement in teachers’ understanding of deep learning principles, enhanced ability to design and utilize interactive digital learning media, as well as increased student motivation and active participation in the learning process. . The evaluation results showed very positive responses from both teachers and students toward the materials, methods, and media used. Overall, this program contributed significantly to improving the quality of learning in elementary schools and fostering an adaptive learning ecosystem aligned with the demands of 21st-century education.